2008
DOI: 10.1016/j.neuropharm.2008.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Imidazenil: A low efficacy agonist at α1- but high efficacy at α5-GABAA receptors fail to show anticonvulsant cross tolerance to diazepam or zolpidem

Abstract: SUMMARYWhereas advances in the molecular biology of GABA A receptor complex using knock-out and knockin mice have been valuable in unveiling the structure, composition, receptor assembly, and several functions of different GABA A receptor subtypes, the mechanism(s) underlying benzodiazepine (BZ) tolerance and withdrawal remain poorly understood. Studies using specific GABA A receptor subunit knock-in mice suggest that tolerance to sedative action of diazepam requires long-term activation of α1 and α5 GABA A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 40 publications
6
29
0
Order By: Relevance
“…Vlainić and Peričić (2009) [10] demonstrated development of anticonvulsant and sedative tolerance after repeated (10 days) zolpidem treatment in mice. Similar results were obtained in rats [11] . Several studies have also suggested that zolpidem has a significant risk of abuse and dependence in humans [12] .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Vlainić and Peričić (2009) [10] demonstrated development of anticonvulsant and sedative tolerance after repeated (10 days) zolpidem treatment in mice. Similar results were obtained in rats [11] . Several studies have also suggested that zolpidem has a significant risk of abuse and dependence in humans [12] .…”
Section: Introductionsupporting
confidence: 89%
“…Previous studies on mice [10] and rats [11] suggested that, upon repeated treatment, zolpidem produced tolerance to its anticonvulsive and sedative effects. Therefore, zolpidem has a higher abuse potential than previously suggested [12] .…”
Section: Wwwchinapharcom Vlainić J Et Almentioning
confidence: 97%
“…Therefore α1-sparing compounds will certainly not be suitable for all indications. However, imidazo-BDZ carboxamide derivatives (e.g., imidazenil) are α1-sparing compounds that have been shown to have anxiolytic and anticonvulsant actions without (at least so far) demonstrating tolerance and dependence liabilities in monkeys [87] and in rodents [88,89] (Table 1). As such, it may therefore be possible to dissociate anxiolysis from addictive liability, which would have important clinical ramifications for the effective treatment of anxiety-related disorders.…”
Section: Blueprint For Designing a Bdz Without Addiction Liabilitymentioning
confidence: 99%
“…However, mice treated repeatedly with zolpidem, similar to those treated repeatedly with diazepam, have been found to develop tolerance to its sedative and anticonvulsant effects (Vlainić and Peričić, 2009). Similar results were obtained in rats (Auta et al, 2008). In addition, the World Health Organization reports that the frequency of zolpidem abuse and dependence is similar to that of benzodiazepines.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, Holt et al (1997), who studied the effects of zolpidem treatment in rats, reported that the effects on GABA A receptor gene expression in the cortex depended on the exposure time: the effect obtained after 7 days (increased level of α4 mRNA) markedly differed from that observed after 14 days (decreased level of α1 mRNA). Decreased expression of α1 GABA A receptor subunit mRNA was also observed in the prefrontal cortex after treatment of rats with zolpidem for 14 days (Auta et al, 2008).…”
Section: Discussionmentioning
confidence: 85%